Configuration of Man’s Position within Patriarchal Structure in Nepalese Society - Uprety, M. D. (Pragya Darshan प्रज्ञा दर्शन, 2024)
Patriarchy is a powerful philosophy and structure of male domination and supremacy. It is not new, nor is the recognition of women’s demoralized existence well-established patriarchal system and it embraces that there is an inferior position of women since historical period. Patriarchy is a social system in which men use, abuse, control, oppress and exploit women. The concept of patriarchy highlights the interconnection of different aspects of gender discrimination and women are often underprivileged in many areas of social existence. Theories and philosophies of patriarchy explore the division of interests between most men and women formed by the social system of gender perceptions, practices and relationships. Gender is a relationship of power and inequality and not merely of variation. There are various supplementary expressions that have extremely related meaning to patriarchy. These incorporate gender command, gender arrange, gender display and sex-gender formulation. They are comparable in pointing to the powerful interconnection of various sphere of influence of gender discrimination. Analyses of patriarchy differ as to whether men's position as head of the household and family or society or state entity is recognized as the key to their potentiality to rule and oppress, or whether the institutional features of men's supremacy are pictured and imagined. In this context, this study provides an analysis of the understanding and accepting of man's position within existing patriarchal structure in Nepalese societies inside the background of gender standpoints and different educational status. It also tries to explore the common judgments and ruling ideologies on patriarchy and its practices and social insights of gender relationships.